Agreement, Case and Definiteness in Balkan Existential Constructions - Frasson, Alberto (Balcania et Slavia)
This paper discusses agreement and definiteness effects in existential constructions in Balkan existentials constructions. I build on the restriction on definiteness properties of existential pivots known as definiteness effect: post-copular pivots in existentials have to be indefinite. In Balkan languages, the contrast is also signaled by the use of a dedicated copula exhibiting singular neuter agreement. I argue that existential pivots are interpreted as semantic objects, as evidenced by the assignment of non-nominative case. I propose that existential copulas take two nominals: the post-copular pivot and a pre-copular null expletive, which behaves as the subject of the construction.